Never flinch : a novel - King, Stephen, 1947- (London ; India : Hodder & Stoughton ; Manipal Technologies, 2025)
"From master storyteller Stephen King comes an extraordinary new novel with intertwining storylines-one about a killer on a diabolical revenge mission, and another about a vigilante targeting a feminist celebrity speaker-featuring the beloved Holly Gibney and a dynamic new cast of characters. When the Buckeye City Police Department receives a disturbing letter from a person threatening to "kill thirteen innocents and one guilty" in "an act of atonement for the needless death of an innocent man," Detective Izzy Jaynes has no idea what to think. Are fourteen citizens about to be slaughtered in an unhinged act of retribution? As the investigation unfolds, Izzy realizes that the letter writer is deadly serious, and she turns to her friend Holly Gibney for help. Meanwhile, controversial and outspoken women's rights activist Kate McKay is embarking on a multi-state lecture tour, drawing packed venues of both fans and detractors. Someone who vehemently opposes Kate's message of female empowerment is targeting her and disrupting her events. At first, no one is hurt, but the stalker is growing bolder, and Holly is hired to be Kate's bodyguard-a challenging task with a headstrong employer and a determined adversary driven by wrath and his belief in his own righteousness. Featuring a riveting cast of characters both old and new, including world-famous gospel singer Sista Bessie and an unforgettable villain addicted to murder, these twinned narratives converge in a chilling and spectacular conclusion-a feat of storytelling only Stephen King could pull off. Thrilling, wildly fun, and outrageously engrossing, Never Flinch is one of King's richest and most propulsive novels"--
Keywords: Women detectives -- Fiction; Murder -- Fiction; Revenge -- Fiction; Vigilantes -- Fiction; Bodyguards -- Fiction; Thrillers (Fiction); Horror fiction; Novels